Exploring youth and caregiver preferences for asthma education video content - Geryk, Lorie L. (J Asthma, 2015)
OBJECTIVE: This study examines: 1) whether youth and their caregivers have different preferences for asthma education video topics and 2) if education topic preferences vary by youth and caregiver sociodemographic characteristics. METHODS: Youth (n=83) ages 7–17 years with persistent asthma and their caregivers were recruited at two pediatric practices in North Carolina. Sociodemographic information and youth and caregiver preferences for 9 asthma video education topics were collected during in-person interviews. Bonferroni-corrected chi-square or McNemar tests (α=0.0056) were used to compare youth and caregivers differences in topic preferences and topic preferences by youth and caregiver sociodemographic characteristics, including gender, race, ethnicity, and age. RESULTS: Youth were primarily male (52%) and from low-income families (74%; caregiver annual income less than $30,000) and many were Hispanic (45%). Youth and parents expressed the most interest in the following two topics: “how to deal with triggers” (90% and 95%, respectively) and “how to keep asthma under control” (87% and 96%, respectively). Caregivers and children were discordant for two topics: “the difference between a rescue and controller medicine” and “how to [help your child] talk to your [his/her] friends about asthma.” No differences were found between youth and caregiver sociodemographic characteristics and video topic preferences. CONCLUSIONS: Youth with persistent asthma and their caregivers differed in their asthma education topic preferences, but preferences did not vary by caregiver or youth sociodemographic characteristics. Studies examining the effectiveness of interventions tailored to differences in educational preferences of youth with asthma and their caregivers are needed.